2020
DOI: 10.1002/ccd.29430
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of rotational atherectomy versus orbital atherectomy for the treatment of heavily calcified coronary stenosis: A systematic review and meta‐analysis

Abstract: Introduction The optimal approach to deal with severe coronary artery calcification (CAC) during percutaneous coronary intervention (PCI) remains ill‐defined. Methods We conducted an electronic database search of all published studies comparing Orbital versus Rotational Atherectomy in patients undergoing PCI. Results Eight observational studies were included in the analysis. Overall, there were no significant differences in Major‐adverse‐cardiac‐events/MACE (OR: 0.81, CI: 0.63–1.05, p = .11), myocardial‐infarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
0
7
1
Order By: Relevance
“…A meta-analysis including 8 observational trials and a total of 4,332 patients demonstrated no significant difference in overall all-cause death, major adverse cardiac events, myocardial infarction and target vessel revascularization between rotational and orbital atherectomy. 62) The analysis did, however, report a higher rate of coronary dissections (odds ratio [OR], 2.61, p=0.003) and perforations (OR, 2.79, p=0.03) among patients treated with orbital atherectomy. It is unclear if these risks are device or operator technique related.…”
Section: Specific Strategies In Calcium Modificationmentioning
confidence: 96%
“…A meta-analysis including 8 observational trials and a total of 4,332 patients demonstrated no significant difference in overall all-cause death, major adverse cardiac events, myocardial infarction and target vessel revascularization between rotational and orbital atherectomy. 62) The analysis did, however, report a higher rate of coronary dissections (odds ratio [OR], 2.61, p=0.003) and perforations (OR, 2.79, p=0.03) among patients treated with orbital atherectomy. It is unclear if these risks are device or operator technique related.…”
Section: Specific Strategies In Calcium Modificationmentioning
confidence: 96%
“…Multiple studies have shown good outcomes of OA in de novo coronary lesions (Table 2). [25][26][27] In a meta-analysis of 8 studies (4332 patients) comparing RA with OA, 28 compared with nonatherectomy patients, which may be associated with higher rates of vascular complications, major bleeding, and acute kidney injury. 29 Slow-flow/no-reflow and burr entrapment are other complications associated with RA in particular, but their incidence has decreased over time.…”
Section: Suitable For Atherectomy?mentioning
confidence: 99%
“…In a meta‐analysis of 8 studies (4332 patients) comparing RA with OA, 28 OA was associated with lower long‐term (1 year) MACE (odds ratio [OR]: 0.66; 95% confidence interval [CI]: 0.44, 0.99; p = 0.04), long‐term target‐vessel revascularization (OR: 0.40; 95% CI: 0.18, 0.89; p = 0.03), and short‐term (in‐hospital and 30‐day) myocardial infarction (OR: 0.64; 95% CI: 0.44, 0.94; p = 0.02). On the other hand, OA was associated with more angiographic complications, including coronary artery dissections (OR: 2.61; 95% CI: 1.38, 4.92; p = 0.003) and device‐related coronary perforations (OR: 2.79; 95% CI: 1.08, 7.19; p = 0.03).…”
Section: Introductionmentioning
confidence: 99%
“…Experience has shown that both OA and RA are effective and most patients could be successfully treated using either. Several small, non‐randomized studies comparing RA and OA have been followed by meta‐analyses, the most recent of which is found in this issue of Catheterization and Cardiovascular Interventions 1 …”
Section: Outcome Of Interest 0–30 Days 30 Days–1 Year 0 Days–1 Yearmentioning
confidence: 99%
“…Khan et al included 3048 RA patients and 1284 OA patients in their meta‐analysis 1 . They defined nine “outcomes of interest” with a total of 17 endpoints (Table 1).…”
Section: Outcome Of Interest 0–30 Days 30 Days–1 Year 0 Days–1 Yearmentioning
confidence: 99%